Late Archean geologic history of the Nain Province, North River-Nutak map area, Labrador, and its tectonic significance - Van Kranendonk, Martin J.; Helmstaedt, Herwart (Geoscience Canada, 1990)
The high-grade gneisses of the Archean Nian Province were formed through Early and Late Archean orogenic cycles. Late Archean structural development consisted of pre-thermal-peak isoclinal folding and thrusting in allochthonous Upernavik supra-crustal rocks, followed by regional, recumbent, isoclinal folding and upright refolding of the Upernavik suite and reworked Early Archean gneisses under amphibolite- to granulite-facies conditions. Style and sequence of the Late Archean structures closely resemble those described by previous workers from the Early Archean gneiss complex of the North Atlantic craton, from Precambrian greenstone belts, and from Phanerozoic orogenic belts, suggesting that no principal differences exist in the structural evolution of these types of terrain.